Financial Literacy and Financial Wellbeing of Public Sector Employees: A Critical Literature Review - Kamakia, Margaret Gatuiri; Mwangi, Cyrus Iraya; Mwangi, Mirie (European Scientific Journal, ESJ, 2017)
There is a great concern from researchers, government, and professional bodies about how consumers, households, students and employees manage their finances. A great number of people from both developed and developing countries are reported to be financially illiterate. Employees today are facing serious challenges in financial decision making that seems to emanate from the changes in financial markets and in social security pension schemes. They have access to financial literacy sessions at their workplaces yet this is not always reflected in the kind of lives they live. This provokes the question ‘does a more financially literate employee enjoy better financial wellbeing than a less literate person?’ The current study therefore seeks to critically review the literature to establish the documented relationship between financial literacy and financial wellbeing and possible intervening and moderating variables. The existing literature gaps are identified and recommended for further research. The results from the literature review indicate that financial literacy and financial wellbeing are defined and measured differently. Additionally, there seem to be a positive relationship between financial literacy and financial wellbeing but this relationship is intervened and moderated by financial decisions and demographic factors respectively.